Instagram Captions in Enhancing Students' Argumentative Writing Abilities - Novia Ramadhini Luthfyani; Mutiarani (LPPM Universitas Islam Darul `Ulum Lamongan, 2026)
This research examines how effective Instagram captions are in enhancing the argumentative writing skills of students at SMA An-Nurmaniyah in Ciledug, Tangerang. This research employs a quantitative pre-experimental design that includes a single group with pre-test and post-test measurements, involving 35 students from the tenth grade. This research measured students’ argumentative writing skills before and after the treatment where Instagram captions were utilized as a tool. The findings revealed a significant improvement, with the mean score increasing from 29.89 to 52.17 and a significance value of 0.00 (<0.05), indicating that Instagram captions effectively help students to boost their argumentative writing skills. This feature of Instagram can directly connect students with others to give their arguments with a well-argumentative structure, which can train their argumentative writing skills. Therefore, it can be concluded that the use of Instagram captions as effective and interactive media enhance students’ argumentative writing skills in English learning. Keywords: English writing skills, Argumentative Writing, Social Media, Instagram Captions, Quantitative Research.